Digital Marketing Transformation: Opportunities and Obstacles for Bali's Small and Medium Industries - I Gusti Agung Ketut Gede Suasana; Anak Agung Gede Suarjaya; Ketut Juliartini (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2025)
Small and medium-sized industries (SMIs) typically have difficulty adapting technology to digital marketing changes due to limited resources. The study explains the ability of SMI to transform marketing into digital business processes. The study is quantitative, and the data was analysed with SmartPLS using a sample of 180 SMI entrepreneurs in Bali. It has been found that internal and external factors significantly influence digitisation, and digitalisation significantly influences changes in digital marketing. Internal factors are the best predictors of digitisation and are the basis of digitalisation and digital marketing transformation. Average online sales for SMI devices are higher than usual. SMI entrepreneurs are advised to adopt strategies that increase the capacity of their internal resources to embrace the evolution of digital technology because internal resources are the leading force in adopting digital technology to transform marketing activities.